Relevansi Kaidah Al-Yaqin La Yuzalu Bi Al-Syakk di Era Ekonomi Digital - Neyza Aqwa Ribut Zaskia; Rafelian Reza Anggara; Ananda Akbar Pradana; Abdul Waarits Ibrahim Sukri; Mokhamad Rachmad Tullah Akbar; Mochamad Andhika Rasendrya Saputra; Taufiq Kurniawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to examine the Islamic legal maxim al-yaqīn lā yuzālu bi al-syakk (certainty is not removed by doubt), along with its foundations, branches, and applications in the context of Islamic economics. This maxim plays a crucial role in Islamic legal rulings as it provides guidance that something already established with certainty cannot be nullified merely by subsequent doubt. This research adopts a literature review method by analyzing the Qur’an, hadiths, and various recent academic references. The findings indicate that this legal maxim safeguards legal certainty, prevents decision-making based on mere speculation, and protects individual rights in transactions. Several derivative principles, such as al-ashlu baqā’ mā kāna ‘alā mā kāna, al-ashlu barā’atu al-dzimmah, and al-ashlu fil asy-ya’ al-ibāhah, reinforce the notion that the original legal status remains valid until proven otherwise by strong evidence. Its application in Islamic economics covers trade transactions, mudharabah contracts, asset ownership, and debt settlement, all of which require valid proof before altering an established legal status. This study concludes that implementing the maxim al-yaqīn lā yuzālu bi al-syakk remains highly relevant in the context of modern economic development, as it ensures fairness, minimizes disputes, and promotes secure and sharia-compliant transactions.